MicroRNA-214 Suppresses Growth and Invasiveness of Cervical Cancer Cells by Targeting UDP-N-acetyl-α-d-galactosamine:Polypeptide N-Acetylgalactosaminyltransferase 7 - Peng, Rui-Qing (American Society for Biochemistry and Molecular Biology, 2012)
MicroRNAs are a class of small noncoding RNAs that function as key regulators of gene expression at the post-transcriptional level. In this study, we demonstrate that miR-214 is frequently down-regulated in cervical cancer, and its expression reduces the proliferation, migration, and invasiveness of cervical cancer cells, whereas inhibiting its expression results in enhanced proliferation, migration, and invasion. miR-214 binds to the 3′-UTR of UDP-N-acetyl-α-d-galactosamine:polypeptide N-acetylgalactosaminyltransferase 7 (GALNT7), thereby repressing GALNT7 expression. Furthermore, we are the first to show, using quantitative real-time PCR, that GALNT7 is frequently up-regulated in cervical cancer. The knockdown of GALNT7 markedly inhibits cervical cancer cell proliferation, migration, and invasion, whereas ectopic expression of GALNT7 significantly enhances these properties, indicating that GALNT7 might function as an oncogene in cervical cancer. The restoration of GALNT7 expression can counteract the effect of miR-214 on cell proliferation, migration, and invasiveness of cervical cancer cells. Together, these results indicate that miR-214 is a new regulator of GALNT7, and both miR-214 and GALNT7 play important roles in the pathogenesis of cervical cancer.